Effectiveness of Adaptive Learning Platforms in Accommodating Student Learning Styles - RN, Bustanul Iman (International Journal of Instructional Technology, 2023)
This study aims to evaluate the effectiveness of adaptive learning platforms in accommodating students' learning styles and their impact on learning outcomes, motivation, and student engagement. The focus of this research is to understand how the personalization offered by adaptive platforms can enhance the quality of education by providing a learning environment tailored to individual needs.The research method used is a qualitative approach with a phenomenological research type, involving in-depth interviews and participant observations of students at SMK Pelayaran Samudera Nusantara Utama Palopo. The results indicate that the adaptive learning platform has a significant positive impact on material comprehension, improved learning outcomes, as well as on student motivation and engagement in the learning process. The flexibility and accessibility provided by the platform also enable students to learn in a manner that is more comfortable and suited to their needs.The implications of this study suggest that integrating adaptive technology in education can be an effective solution for addressing differences in students' learning styles. However, further comprehensive research is needed to explore the application of this technology across various educational contexts.